MHD ternary (Ag–CuO–SWCNT) blood-based Jeffrey nanofluid flow with surface catalyzed reaction - A. S. Ashwinth Jeffrey; M. Shanmugapriya; R. Sundareswaran; U. Fernandez-Gamiz (AIP Advances)
The present study aims to investigate the effects of MHD non-Newtonian Jeffrey ternary hybrid nanofluid flow over a porous moving wedge with surface-catalyzed homogeneous–heterogeneous chemical reactions. To analyze the energy transmission rate, this study considers the prominent nanoparticles silver (Ag), cupric oxide (CuO) and single-walled carbon nanotube (SWCNT) suspended in blood, which serves as the base fluid. In this fluid flow problem, the momentum, energy, concentration, and mass diffusion are inspected under the influence of a magnetic field, thermal radiation, activation energy with binary chemical reactions, thermophoresis, and Brownian motion. The present study is significant due to its potential to improve heat transfer, catalysis, energy efficiency, and biomedical applications. To model this flow mathematically, a system of partial differential equations (PDEs) is formulated and subsequently transformed into non-dimensional ordinary differential equations using suitable similarity variables. The shooting technique is implemented in MATLAB to obtain the numerical solutions for the dragging force (Cfx), energy transmission rate (Nux), rate of mass transport S h x , and mass fluxes S h A and S h B . This study reveals that an increase in the porous medium parameter (Kp) reduces the velocity profile, while an increase in the Jeffrey fluid parameter (λ1) enhances it. The volume fraction parameters (φAg, φCuO, φSWCNT), Brownian motion parameter (Nb) and thermophoresis parameter (Nt) contribute to an increase in temperature. This study concludes that (Ag + CuO + SWCNT/Blood) exhibits superior heat transfer capabilities and it achieves a 7.79% higher energy transmission rate than (CuO + SWCNT/Blood), 10.76% higher than (SWCNT/Blood) and 11.31% higher than the blood.